Potencjał edukacyjny szkoły a strategie adaptacji uczniów - Murawska, Iwona; Przyborowska, Beata (Studia Edukacyjne, 2020)
Murawska Iwona, Przyborowska Beata, Potencjał edukacyjny szkoły a strategie adaptacji uczniów [Educational Potential in Schools and Students’ Adaptation Strategies]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 27-38. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.2 In the article below, We explore the level of strategies of modern youth, in the context of various ways of adapting to school and being a student in schools of diverse educational potential. For research purposes, We have used an original, five-stage scale to measure student strategies. We developed the scaled based on the Theory of Social Adaptation by R. K. Merton. Adaptation can be implemented through attitudes of conformity, innovation, ritualism, retreatism and rebellion. The analysis presented is part of a larger project on youth adaptation strategies. The results obtained show the differences in the occurrence of strategies in different types of schools.